Socioeconomic and Demographic Disparities in Early Surgical Stabilization Following Emergency Department Presentation for Shoulder Instability - Steven L. Bokshan, M.D; Lambert T. Li, B.A; Nicholas J. Lemme, M.D; Brett D. Owens, M.D (Elsevier, 2021)
Purpose: To describe which patients are the most likely to undergo surgical management within the same calendar year as their emergency department visit for anterior shoulder instability. Methods: The State Emergency Department Databases and State Ambulatory Surgery and Services Databases from Florida were used. All patients presenting to the emergency department for anterior shoulder subluxation or dislocation between January 1 and September 30, 2017, were selected. Bivariate analysis was performed for associations with demographic variables. A binary logistic regression was performed with all significant factors to assess which were predictors of undergoing surgery the same calendar year. Results: While controlling for all significant factors, we found that patients with recurrent dislocations were 3.14 times more likely to have surgery within the same year (P = .037). Patients younger than 40 years were also 2.04 times more likely to have surgery than those aged 40 years or older (P < .001). White patients were 2.47 times more likely to have surgery than black patients (P < .001). On bivariate analysis, there was an association between greater income quartile and higher odds of undergoing surgery within 30 days. Conclusions: Following an emergency department visit for acute shoulder instability, the following variables were associated with undergoing surgical stabilization within the same calendar year: previous dislocation, age younger than 40, and white race. Patients living in the greatest income quartile of patients had a significantly greater percentage of patients having surgery within 30 days. This demonstrates that disparities and barriers to care may exist for patients with shoulder instability. Level of Evidence: Level III, Retrospective Comparative Study.